A high-entropy catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202610820342.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-08
- Publication Date
- 2026-10-30
AI Technical Summary
但在颗粒化过程中,成型压力与粘结剂的引入往往会大幅降低比表面积,产生严重的传质阻力,导致催化效率急剧下降
本申请的高熵催化剂,通过在框架材料中引入CuO、MnO2和Fe2O3中的至少一种作为表面电子环境调节材料,能够调节催化剂的表面电子环境,优化相结构,进而提高过硫酸盐激活效率及催化剂的稳定性。
Smart Images

Figure CN122999204A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of high-entropy oxide materials technology, and in particular to a high-entropy catalyst, its preparation method, and its application. Background Technology
[0002] With the rapid development of the medical and aquaculture industries, the accumulation of emerging antibiotic pollutants in the aquatic environment has become a global ecological challenge. Ciprofloxacin, a typical fluoroquinolone antibiotic, is frequently detected in wastewater treatment systems due to its structural stability, poor biodegradability, and potential ecotoxicity. Advanced persulfate-based oxidation technologies, with their generated strong oxidizing free radicals, are considered an effective means of degrading this type of pollutant.
[0003] The oxidation efficiency of persulfate systems is highly dependent on the catalyst. Currently, traditional single metal oxides such as spinel suffer from problems such as limited active sites, single electron transfer pathways, and insufficient structural stability, which easily lead to the dissolution of metal ions and secondary pollution.
[0004] High-entropy oxides, with their entropy stabilization effect and lattice distortion resulting from the random distribution of multiple components, can provide abundant interfacial defects and multivalent state synergistic systems, exhibiting excellent intrinsic activity in activating persulfate. However, existing research on high-entropy catalysts mainly focuses on powder morphology. Not only is the mechanism by which sintering temperature controls the crystal phase in the preparation process unclear, but powder materials are also easily lost in actual wastewater and difficult to recover, severely limiting their engineering application in large-scale water treatment.
[0005] To address the challenge of recovering powdered catalysts, granulation is considered a key approach. However, during granulation, the molding pressure and the introduction of binders often significantly reduce the specific surface area, generating severe mass transfer resistance and leading to a sharp decline in catalytic efficiency. Furthermore, sacrificing mechanical strength for high porosity often results in particles that are easily broken under stirring and collision.
[0006] Therefore, how to construct a particulate catalytic system that combines efficient mass transfer pathways and high mechanical strength while ensuring the intrinsic activity of high-entropy materials is a key technical challenge that urgently needs to be overcome in the field of advanced oxidation technology. Summary of the Invention
[0007] The purpose of this application is to provide a novel high-entropy catalyst, its preparation method, and its application.
[0008] The following technical solution is adopted in this application: One aspect of this application discloses a high-entropy catalyst, which is composed of a framework material and a surface electronic environment conditioning material; wherein the framework material includes MgO, Co3O4, NiO and ZnO; and the surface electronic environment conditioning material is at least one of CuO, MnO2 and Fe2O3.
[0009] It should be noted that the high-entropy catalyst of this application, by introducing CuO, MnO2, or Fe2O3 surface electronic environment conditioning materials into the framework material, can regulate the surface electronic environment of the catalyst, optimize the phase structure, and thus improve the persulfate activation efficiency and catalyst stability. The surface electronic environment conditioning material can be any one of CuO, MnO2, and Fe2O3, or a combination of at least one of MnO2 and Fe2O3 with CuO; the introduction of Mn or Fe contributes to the formation of a two-phase structure, while Cu mainly forms the rock salt phase.
[0010] In some implementations, the amount of surface electronic environment conditioning material is 15 to 35 wt% of the frame material weight.
[0011] In some implementations, the framework material is composed of MgO, Co3O4, NiO, and ZnO.
[0012] In some implementations, the weight ratio of MgO, Co3O4, NiO and ZnO is 1:(1.6~2.6):(1.4~2.4):(1.6~2.6).
[0013] In some implementations, the high-entropy catalyst has a particulate structure.
[0014] In some implementations, the high-entropy catalyst is a porous particle.
[0015] In some implementations, the pore size of the high-entropy catalyst particles with porous structures is 12-55 nm.
[0016] In some implementations, the pore volume of the high-entropy catalyst particles with porous structures is 0.01–0.09 cm³. 3 / g.
[0017] In some implementations, the particle size of the high-entropy catalyst particles is 0.4-1.25 mm.
[0018] Another aspect of this application discloses a method for preparing the high-entropy catalyst of this application, comprising the following steps: (1) Obtain the oxide powders of the framework material and the surface electronic environment conditioning material, mix them, and obtain the high-entropy catalyst powder; (2) Mix the high-entropy catalyst powder with the pore-forming agent to obtain a mixed powder. Press the mixed powder into tablets to obtain a sheet-like blank. Crush the sheet-like blank and classify and sieve it according to the required particle size of the high-entropy catalyst particles to obtain a particle blank. (3) Heat treatment is performed on the particle blank, that is, the temperature is raised to 500-550 ℃ at 2-20 ℃ / min and held for 20-120 min, then the temperature is raised to 700-1100 ℃ at 2-20 ℃ / min and held for 1-12 h, then the temperature is lowered to 500-550 ℃, and then the temperature is lowered to room temperature to obtain the high entropy catalyst particles of this application.
[0019] Preferably, in step (3), the temperature is increased to 500-550 ℃ at 2-20 ℃ / min and held for 20-120 min, and then increased to 900-1100 ℃ at 2-20 ℃ / min and held for 1-5 h, which can obtain a high-entropy catalyst with better catalytic effect.
[0020] It should be noted that this application innovatively mixes high-entropy catalyst powder with a pore-forming agent for tableting, followed by crushing into the desired particles. The advantage of this method is that the mechanical strength of the particles is significantly improved through tableting and subsequent crushing, effectively ensuring the stability and recyclability of the catalyst during the reaction process. Furthermore, the addition of a pore-forming agent can compensate for the potential loss of specific surface area during the powder-to-particle conversion process and enhance catalytic performance by optimizing the pore structure. This process design fully utilizes the promoting effect of the pore structure on the catalytic reaction while ensuring particle strength. While the use of pore-forming agents is not uncommon in catalyst preparation, this application's method of mixing high-entropy catalyst powder with a pore-forming agent for tableting, combining tableting and crushing, achieves a good balance between mechanical strength and catalytic activity, thereby enhancing the catalyst's performance and stability.
[0021] It should also be noted that the preparation method of this application optimizes and refines each step of the heat treatment of the particulate preform, such as the temperature rise rate and holding time, so that the high entropy catalyst of this application can achieve the best catalytic performance and structural characteristics. In particular, the choices made in this application regarding specific temperature control and time control are based on a comprehensive consideration of catalyst performance, ensuring the stability and excellent performance of the catalyst in efficient catalytic degradation reactions.
[0022] In some implementations, step (1) further includes mixing the oxide powders, dispersion media and grinding balls at a mass ratio of 1:(2~4):(4~6), and ball milling at a speed of 200-600 r / min for 4-24 hours to achieve preliminary mixing and refinement of the raw materials; after ball milling, drying the mixture, grinding and passing it through a 40-100 mesh sieve to obtain raw material powder; heating the raw material powder to 700-1100 ℃ at a heating rate of 2-20℃ / min for 1-4 hours for heat treatment, and after natural cooling, fully grinding the sintered product and passing it through a 40-100 mesh sieve to finally obtain high-entropy catalyst powder.
[0023] It should be noted that in the preparation method of this application, the heating rate of steps (1) and (3) is 2-20 ℃ / min, which can be 2 ℃ / min, 5 ℃ / min, 8 ℃ / min, 10 ℃ / min, 13 ℃ / min, 15 ℃ / min, 18 ℃ / min or 20 ℃ / min. In some implementations, 5 ℃ / min is specifically used.
[0024] In some implementations, the pore-forming agent in step (2) is corn starch.
[0025] In some implementations, the amount of pore-forming agent used is 3-9 wt% of the total weight.
[0026] In some implementations, the tableting process in step (2) is performed under a pressure of 1-20 MPa for 1-5 min.
[0027] Another aspect of this application discloses the application of the high-entropy catalyst of this application in the activation of persulfate degradation of ciprofloxacin.
[0028] It should be noted that the key improvement of the high-entropy catalyst in this application is to enhance the activation efficiency of persulfate and the stability of the catalyst; therefore, the high-entropy catalyst in this application can be used to activate persulfate to degrade ciprofloxacin.
[0029] Another aspect of this application discloses a reagent for activating persulfate, which contains the high-entropy catalyst of this application.
[0030] It should be noted that the reagent for activating persulfate in this application, due to the presence of the high-entropy catalyst of this application, can improve the activation efficiency of persulfate and the stability of the catalyst. It is understood that the key to the reagent for activating persulfate in this application lies in the presence of the high-entropy catalyst of this application. Based on this, it is not excluded that other conventionally used reagents may be added in combination to further enhance or improve catalytic performance and / or stability; no specific limitations are made here.
[0031] The beneficial effects of this application are as follows: The high-entropy catalyst of this application, by introducing at least one of CuO, MnO2 and Fe2O3 as a surface electronic environment regulating material into the framework material, can regulate the surface electronic environment of the catalyst, optimize the phase structure, and thus improve the persulfate activation efficiency and the stability of the catalyst. Attached Figure Description
[0032] Figure 1 These are the degradation curves of the high-entropy catalysts in experiments 1 to 3 in the embodiments of this application, wherein (a) is the degradation curve of experiments 1 to 3, (b) is the cyclic degradation curve of experiment 1, (c) is the cyclic degradation curve of experiment 2, and (d) is the cyclic degradation curve of experiment 3. Figure 2 These are the XRD diffraction patterns of the high-entropy catalysts in Experiments 1 to 3 of the embodiments of this application; Figure 3 These are the XPS photoelectron spectra of the high-entropy catalysts in experiments 1 to 3 of this application, wherein (a) is Mg 1s, (b) is Co 2p, (c) is Ni 2p, (d) is Zn 2p, (e) is Cu 2p, (f) is Mn 2p, (g) is Fe 2p, and (h) is O 1s; Figure 4 These are the XRD diffraction patterns of the high-entropy catalysts in experiments 4 to 8 of the embodiments of this application; Figure 5 These are SEM morphology images of the high-entropy catalysts in experiments 4 to 8 of this application, wherein (a) is at 700℃, (b) is at 800℃, (c) is at 900℃, (d) is at 1000℃, and (e) is at 1100℃. Figure 6 These are the cyclic degradation curves of the high-entropy catalysts in experiments 4 to 8 of the embodiments of this application; Figure 7 These are the cyclic degradation curves of the high-entropy catalysts prepared for different heat preservation times in the embodiments of this application; Figure 8 These are the cyclic degradation curves of the high-entropy catalysts in experiments 9 to 12 of this application, wherein (a) is the degradation curve of experiments 9-12, (b) is the cyclic degradation curve of experiment 9, (c) is the cyclic degradation curve of experiment 10, (d) is the cyclic degradation curve of experiment 11 and (e) is the cyclic degradation curve of experiment 12, and (f) is the cyclic mass loss rate of the high-entropy catalysts in experiments 9 to 12. Figure 9These are the cyclic degradation curves of the high-entropy catalysts in experiments 13 to 17 of this application, wherein (a) is the degradation curve of experiments 13-17, (b) is the cyclic degradation curve of experiment 13, (c) is the cyclic degradation curve of experiment 14, (d) is the cyclic degradation curve of experiment 15, (e) is the cyclic degradation curve of experiment 16 and (f) is the cyclic degradation curve of experiment 17, and (g) is the cyclic mass loss rate of the high-entropy catalysts in experiments 13 to 17. Figure 10 The images show the structural characterization of the high-entropy catalyst after cycling in Experiment 15 of this application, where (a) is a SEM image and (b) is an XRD image. Detailed Implementation
[0033] To address the technical challenges of low degradation efficiency, difficult recovery of powdered catalysts, and insufficient stability of recalcitrant organic pollutants such as ciprofloxacin in persulfate systems, this application proposes a high-entropy oxide particulate catalyst and its preparation method. This application uses MgO, Co3O4, NiO, and ZnO as the main components, and introduces Cu, Mn, and Fe to adjust the surface electronic environment. A particulate catalyst with a rock salt-spinel dual-phase structure is prepared using a solid-state reaction method combined with a dry granulation process. This application achieves a balance between ion diffusion and activity defects through precise control of the sintering temperature, and constructs a multi-level porous structure by introducing a pore-forming agent to improve mass transfer efficiency. The particulate catalyst prepared in this application exhibits excellent performance in the activation of persulfate for the degradation of ciprofloxacin. In some implementations, its initial degradation rate can reach 97%, and it retains more than 94.1% of its activity after 5 cycles. Simultaneously, the particles have extremely high mechanical strength, with a cycle mass loss of only 8%, and the metal ion dissolution level is far below environmental standards. This application not only achieves a balance between high activity and high stability of high-entropy catalytic materials, but also solves the recycling problem through granular design, providing an efficient, stable and sustainable engineering solution for the deep treatment of antibiotic wastewater.
[0034] The hierarchical pore structure was achieved through material design and sintering process control in this application. Under the action of tableting and crushing, the size and distribution of pores were optimized at the micron and nanoscale, thus forming a hierarchical pore structure in the catalyst. This structure formation is not achieved in a single step but is the result of the synergistic effect of multiple processes. Through this process design, this application effectively increases the specific surface area of the catalyst and significantly enhances the mass transfer efficiency of the reactants. The hierarchical distribution of the pore structure can be clearly seen through SEM and other characterization methods, which directly improves the catalytic activity and long-term stability of the catalyst.
[0035] It should be noted that, since the catalyst material in this application is granular, standard mechanical strength testing methods, such as compression or bending tests, are not applicable to granular materials. Converting the material to other shapes for testing may not represent the actual usage and mechanical properties of granular materials; therefore, we did not perform traditional mechanical strength tests. Instead, we indirectly assessed the mechanical strength of the catalyst by repeatedly cycling the catalyst and monitoring the mass loss of the particles. In the experiment, the mass loss of the catalyst particles after multiple uses was only 8%, indicating that the catalyst exhibited good resistance to pulverization and mechanical stability during cycling, which can be considered indirect evidence of the mechanical strength of the granular material. Although standard mechanical strength tests were not performed, we believe that this indirect method can effectively reflect the mechanical stability and long-term durability of the catalyst and has sufficient experimental evidence.
[0036] Compared with existing similar products, the high-entropy catalyst of this application has the following advantages: 1. Highly efficient and stable catalytic performance: This application achieves rapid degradation of pollutants such as ciprofloxacin through the multi-metal synergistic effect of high-entropy components, with a degradation rate exceeding 97%. Simultaneously, the high-entropy effect enhances the chemical stability of the material, effectively inhibiting the dissolution of metal ions and reducing the risk of secondary pollution.
[0037] 2. High mechanical strength and durability: The dry granulation process and specific sintering regime create a dense skeletal structure within the granular catalyst, significantly enhancing the material's mechanical strength. This makes the catalyst less prone to breakage under stirring and impact conditions, with a mass loss of only about 8% after 5 cycles, greatly extending its service life.
[0038] 3. Facilitates recycling and engineering applications: This application transforms powder materials into granular form, completely solving the technical bottleneck of easy loss and difficult recycling of powder catalysts. By optimizing particle size and pore-forming agent content, efficient solid-liquid separation is achieved while maintaining high activity, significantly reducing operating costs and improving the economics and feasibility of engineering applications.
[0039] The present application will be further described in detail below through specific embodiments. The following embodiments are only for further explanation of the present application and should not be construed as limiting the present application.
[0040] Unless otherwise specified, all materials and reagents used in the following examples are commercially available, and all experimental methods used in the following examples are conventional methods.
[0041] Example The high-entropy catalyst and its preparation process in this example are as follows: 1. Experimental methods and procedures High-entropy catalyst powder: All raw materials used in this application are analytical grade, using MgO, Co3O4, NiO, ZnO, and one of the metal oxides CuO, MnO2, and Fe2O3 as raw materials. The prepared raw material powder, dispersion medium (such as anhydrous ethanol), and grinding balls are mixed at a mass ratio of 1:(2~4):(4~6) and ball-milled at 200-600 r / min for 4-24 hours to achieve preliminary mixing and refinement of the raw materials. After ball milling, the mixed powder is placed in an oven for drying, and then the dried powder is ground using an automatic grinder and passed through a 40-100 mesh sieve to obtain the raw material powder. The obtained powder is placed in a corundum crucible and heated in a muffle furnace at a heating rate of 2-20 ℃ / min to a target temperature of 700-1100 ℃ for 1-4 hours for heat treatment. After natural cooling, the sintered product is thoroughly ground and passed through a 40-100 mesh sieve to finally obtain the high-entropy catalyst powder.
[0042] High-entropy catalyst particles: High-entropy catalyst powder was mixed uniformly with 1-9 wt% PVA solution. To investigate the effect of additives, different amounts of corn starch (3-9 wt%) were added to the system and thoroughly mixed. The mixed powder was passed through a 60-mesh sieve and pre-dried at 60℃ for 20 min.
[0043] The powder was then placed in a mold and held under pressure of 1-20 MPa for 1 min to prepare a sheet-like green body. The green body was then crushed and graded by sieving through a standard sieve. The sieve apertures used in the particle size study were 16 mesh, 18 mesh, 24 mesh, 30 mesh, and 45 mesh, which yielded particle green bodies with a particle size of approximately 1.25-0.4 mm.
[0044] The particle blanks were then placed in a high-temperature energy-saving electric furnace for heat treatment: the temperature was increased to 500℃ at 2-10℃ / min and held for 20-120 min, then increased to 700-1100℃ and held for 1-12 h, then cooled to 500℃ and then cooled to room temperature, finally obtaining the high-entropy catalyst particles of this application.
[0045] 2. Performance Testing and Characterization The microstructure of the powder was observed using scanning electron microscopy (SEM) to assess its particle size and surface structure. X-ray diffraction (XRD) was used to analyze the crystal phase composition and lattice parameters of the powder to confirm whether it possessed a spinel structure. The specific surface area and pore structure parameters of the powder were determined using nitrogen adsorption-desorption. The elemental valence states of the powder were analyzed using X-ray photoelectron spectroscopy (XPS).
[0046] 3. Catalytic performance determination The catalytic degradation reaction is carried out at room temperature. To optimize reaction efficiency and scalability, the following general operating procedure is recommended, with key parameters scaled up or down proportionally according to the reaction system volume. Add the catalyst at a dosage of 0.05 to 0.5 g per liter of reaction solution to an aqueous solution containing the target pollutant (e.g., ciprofloxacin CIP) at a concentration of 5-50 mg / L. Adjust the initial pH of the system by adding an acid (e.g., H₂SO₄) or a base (e.g., NaOH) solution. Add persulfate (PMS) to the above system to achieve an initial concentration range of 0.5-3.0 mM in the reaction solution. Subsequently, start and maintain the reaction under magnetic stirring at a speed of, for example, 400-1000 r / min, or an equivalent mixing method to ensure system homogeneity. During the reaction, take 1 mL of the reaction solution at set time intervals, filter it through a 0.22 μm PTFE membrane, and immediately add 0.5 mL of Na₂SO₃ solution to terminate the reaction. The concentration of CIP was then quantitatively analyzed using high-performance liquid chromatography (HPLC). The measured CIP concentration was compared with the initial CIP concentration, and the catalytic effect was characterized by the amount or percentage decrease in CIP concentration. All experiments were repeated at least twice to ensure the reliability of the results.
[0047] 4. Stability performance determination After the degradation reaction was completed, samples were taken and filtered through a 0.22 μm PTFE membrane to remove suspended particles. Inductively coupled plasma mass spectrometry was used to determine the concentration change of metal ions in the solution to evaluate the stability of the catalyst and the dissolution of metals during the reaction.
[0048] 5. Reusability test After a single degradation experiment, the catalyst was centrifuged and repeatedly washed with ultrapure water to remove surface residues. It was then dried to constant weight at 80 °C, weighed, and its mass was recorded for use in the next cycle. Through multiple consecutive cycles, the constant weight of the catalyst was recorded after each cycle to analyze the changes in catalyst activity and mass with the number of cycles. The catalyst mass loss rate can be calculated using the following formula:
[0049] Based on the methods described above, this example tests the effects of components, dosages, and certain parameter conditions on the high-entropy catalyst, as detailed below: Experiments 1-3: The Influence of Feed Formulation on Various Performance Aspects of High-Entropy Catalysts (1) Test methods A high-entropy catalyst particle, the preparation method of which includes the following steps: Step 1: Preparation of high-entropy catalyst powder: Weigh and mix the raw materials according to the dosage table, and mix them with anhydrous ethanol and zirconium oxide balls in a mass ratio of 1:3:5. Ball mill in a planetary ball mill for 6 h; dry, grind and sieve to obtain raw material powder; place the powder in a corundum crucible, heat it to 1000℃ in a muffle furnace and hold for 4 h, cool it naturally, grind and sieve to obtain high-entropy catalyst powder.
[0050] Step 2, Preparation of catalyst particles: Mix the powder obtained in Step 1 with 7wt% PVA solution, add 5wt% corn starch, and sieve the mixture; press the powder at 10 MPa for 1 min to form a sheet-like preform, crush it, and then classify it through 24-mesh and 30-mesh sieves to obtain 0.80-0.60 mm particle preforms.
[0051] Step 3: The billet is heated to 500℃ in a high-temperature electric furnace at a heating rate of 5℃ / min and held for 80 min. Then, it is heated to 1000℃ at a heating rate of 5℃ / min and held for 6 h. Finally, it is cooled to 500℃ and allowed to cool naturally to obtain high-entropy catalyst particles.
[0052] The amounts of each raw material used in experiments 1-3 are shown in Table 1.
[0053]
[0054] (2) Test indicators and result analysis Catalytic performance and stability analysis: The catalytic degradation performance, cycle stability, and metal dissolution of Experiments 1, 2, and 3 were analyzed. The results are shown in [Table missing]. Figure 1 Experiments 1-3 showed high-entropy catalytic materials with added Cu, Mn, and Fe metal oxides, respectively. The results indicated that experiment 2 achieved the highest removal rate of ciprofloxacin (96.2%), but exhibited significant activity decay during cycling. Experiment 1 achieved a removal rate of 88.9% for ciprofloxacin, with relatively high metal ion dissolution. Experiment 3 achieved a removal rate of 92.2% for ciprofloxacin, maintaining a degradation efficiency of approximately 87.9% after multiple cycles, and exhibited the lowest metal ion dissolution concentration.
[0055] Table 2. Concentration of leached metal ions after reactions in experiments 1-3
[0056] Crystal phase analysis: Crystal phase analysis was performed on the high-entropy catalyst particles prepared in Experiments 1, 2, and 3. The results are shown in [Figure 1]. Figure 2Experimental results show that when CuO is added, only characteristic peaks of the rock salt structure are detected in the sample, indicating that the sample exists as a single rock salt phase solid solution. Compared with experiments 2 and 3, which added MnO2 and Fe2O3, no obvious spinel characteristic peaks were detected in experiment 1. This is because, under the condition of Cu introduction, the multi-component cations are mainly stable in the octahedral coordination environment. 2+ The presence of octahedral coordination plays an important role in maintaining the structural stability of a single rock salt phase. When experiments 2 and 3 were used, in addition to the rock salt diffraction peaks, characteristic peaks of the spinel structure also appeared in the diffraction patterns of the samples, indicating that the catalytic materials prepared by experiments 2 and 3 exhibit a two-phase structure in which the rock salt phase and the spinel phase coexist.
[0057] Elemental valence state analysis: XPS analysis of elemental valence states and oxygen species composition was performed on Experiments 1, 2, and 3. The results are shown in [Table missing]. Figure 3 Experimental results show that the transition metal components in each experiment exhibit multivalent coexistence characteristics and significant electronic interactions. Among them, the proportion of defect oxygen (oxygen vacancies) in experiments 2 and 3 is significantly higher than in experiment 1, with experiment 3 showing the most prominent proportion. Compared to experiment 1, which exhibits a single rock salt phase, experiments 2 and 3 form a rock salt-spinel dual-phase structure. Due to the structural mismatch and lattice distortion at the phase interface, a high proportion of oxygen defects are enriched. Simultaneously, experiments 2 and 3, by introducing Mn and Fe valence centers, construct a more complex multivalent synergistic system, generating more active sites through a charge compensation mechanism.
[0058] In summary, in this example, the addition of CuO can utilize Cu 2+ The stability in the octahedral coordination environment ensures that the high-entropy oxide exists as a single rock salt phase solid solution, thereby achieving extremely excellent lattice stability and structural integrity, effectively preventing phase transformation or collapse during long-term reaction processes. Although the interface effect of the single rock salt phase is relatively weak, resulting in a slightly lower active site density than the two-phase system, its regular and compact crystal phase arrangement greatly enhances the binding force between the metal component and the lattice, enabling the catalytic material to maintain high structural stability even under harsh environments.
[0059] The addition of MnO2 enables high-entropy oxides to form a significant rock salt-spinel dual-phase structure, through Mn 2 + / Mn 3+ The electronic coupling effect with Co and Ni components in the crystal lattice constructs an efficient electron transport path, promoting charge separation and migration; on the other hand, the introduction of manganese can maintain a more stable and durable catalytic kinetic matching, thereby significantly improving the overall degradation efficiency of high-entropy catalytic materials.
[0060] The addition of Fe2O3 can, on the one hand, induce a high proportion of defect oxygen (oxygen vacancies) in the high-entropy lattice, change the local charge distribution on the surface, and participate in charge exchange as an electron relay station, thereby significantly improving the adsorption and activation performance of the catalytic material for reaction molecules; on the other hand, the introduction of iron can increase the specific surface area of the sample, increase the reaction contact sites, and effectively inhibit the dissolution of metal ions by firmly anchoring the active sites, thus improving the cycling stability of the material.
[0061] Experiments 4-8: Effects of different calcination temperatures on various properties of high-entropy catalyst particles A high-entropy catalyst particle, the preparation method of which includes the following steps: Step 1: Preparation of high-entropy catalyst powder: 5.04 g of MgO, 10.03 g of Co2O3, 9.34 g of NiO, 10.17 g of ZnO and 9.98 g of Fe2O3 were weighed and mixed, and then mixed with anhydrous ethanol and zirconium oxide balls at a mass ratio of 1:3:5. The mixture was ball-milled in a planetary ball mill for 10 h. After drying, the powder was ground and sieved to obtain the raw material powder. The powder was placed in a corundum crucible and heated to temperature T1 in a muffle furnace and held for 2 h. After natural cooling, the powder was ground and sieved to obtain high-entropy catalyst powder.
[0062] Step 2, catalyst particles: Mix the powder obtained in Step 1 with 7 wt% PVA solution, add 5 wt% corn starch, and pass the mixture through a 60-mesh sieve; press the powder at 20 MPa for 1 min to form a sheet-like preform, crush it, and then classify it through 24-mesh and 30-mesh sieves to obtain 0.80-0.60 mm particle preforms.
[0063] Step 3: The billet is heated to 500℃ in a high-temperature electric furnace at a heating rate of 5℃ / min and held for 100 min. Then, it is heated to temperature T1 at a heating rate of 5℃ / min and held for 12 h. Finally, it is cooled to 500℃ and allowed to cool naturally to obtain high-entropy catalyst particles.
[0064] The calcination temperature T1 of the catalyst particles in experiments 4-8 is shown in Table 3.
[0065]
[0066] Crystal phase analysis: From Figure 4The data shows that at 700℃ and 800℃, the diffraction peak intensities of the samples were low and contained fine impurity peaks, indicating that the system was in an incomplete solid solution state. When the sintering temperature rose to 900℃, the impurity phase diffraction peaks basically disappeared, while the characteristic peaks of the rock salt phase and spinel phase significantly increased, indicating that the solid solution reaction between the components was nearing completion, forming a stable two-phase structure. As the temperature further increased to 1000℃ and 1100℃, the diffraction peak intensities continued to increase, and the full width at half maximum (FWHM) decreased. This is because the increased temperature promoted cation diffusion and lattice recombination, continuously increasing the crystallinity of the material and causing the system to evolve towards a high-temperature steady state.
[0067] Microscopic morphology analysis: From Figure 5 The data shows that at 700℃ and 800℃, the grains are in the initial formation stage, with irregular morphology and blurred grain boundaries; when the temperature rises to 900℃, the grain distribution tends to be uniform, the grain boundaries are clear, and the grains exhibit the most uniform characteristics; when the temperature continues to rise to 1000℃ and 1100℃, the grains grow significantly and agglomeration occurs.
[0068] Table 4. Concentration of leached metal ions after activation in experiments 4-8
[0069] Catalytic performance and stability analysis: From Figure 6 The data shows that the catalytic performance of high-entropy catalyst particles initially increases and then decreases with increasing sintering temperature. In this experiment, the sample with the best catalytic performance was sintered at 900℃, achieving a degradation rate of 97%, while the sample sintered at 700℃ only achieved 66.9%. Combined with crystal phase and morphology analysis, this is because a complete two-phase solid solution structure was formed at 900℃, and the particle distribution was the most uniform, providing abundant active sites; while excessively high temperatures led to grain agglomeration, inhibiting the exposure of active sites. Furthermore, Table 4 shows that the leaching amount of metal ions systematically decreases with increasing sintering temperature. This is because increasing the sintering temperature promotes a highly ordered structure and lattice stability, enhancing the anchoring effect on metal ions and thus improving the chemical stability of the material.
[0070] Furthermore, this example investigated the holding time at a heating rate of 5 °C / min to reach temperature T1, with T1 fixed at 1100 °C. The catalytic performance of the high-entropy catalysts prepared after holding for 1 h, 2 h, 3 h, 4 h, and 5 h were tested. The remaining steps and catalytic performance tests were the same as before. The catalytic performance test results for different holding times are shown below. Figure 7 As shown.
[0071] Catalytic performance analysis showed that the catalytic performance of the catalyst particles initially increased and then decreased with prolonged holding time. The sample exhibited optimal catalytic activity, achieving a degradation rate of over 96%, after 2 hours of holding. Analysis suggests that when the holding time was only 1 hour, insufficient diffusion between the multi-metal components and incomplete formation of the high-entropy solid solution structure resulted in a limited number of active sites in the material, leading to weak PMS activation. With a holding time extended to 2 hours, inter-element diffusion became more complete, forming a uniform and stable two-phase solid solution structure while retaining abundant oxygen vacancies and lattice defects, significantly improving electron transport capacity and active species generation efficiency. However, when the holding time was further extended to 3-5 hours, the catalytic performance of the samples gradually decreased. This is mainly because prolonged high-temperature holding promoted further grain growth and sintering densification, leading to increased particle agglomeration, pore shrinkage, and a decrease in specific surface area, thus reducing the exposure of surface active sites and hindering the interfacial reaction between PMS and pollutants. Therefore, a moderate holding time is more conducive to balancing structural stability and surface activity, achieving optimal catalytic performance. This example demonstrates the effect of different holding times tested at 1100 ℃, with the optimal value being 2 h. It can be understood that, based on the aforementioned analysis, if the holding temperature is lowered to 900 ℃, the optimal holding time will be appropriately extended. Further experimental results show that good catalytic performance can be obtained by holding at 900-1100 ℃ for 2-5 h, and the holding time can be shortened accordingly as the temperature increases.
[0072] Experiments 9-12: Effects of different high-entropy catalyst particle sizes on catalytic performance (1) Test methods A high-entropy catalyst particle, the preparation method of which includes the following steps: Step 1: Preparation of high-entropy catalyst powder: 5.04 g of MgO, 10.03 g of Co2O3, 9.34 g of NiO, 10.17 g of ZnO and 9.98 g of Fe2O3 were weighed and mixed, and then mixed with anhydrous ethanol and zirconium oxide balls at a mass ratio of 1:3:5. The mixture was ball-milled in a planetary ball mill for 6 h. After drying, the powder was ground and sieved to obtain the raw material powder. The powder was placed in a corundum crucible and heated to 900℃ in a muffle furnace for 4 h. After natural cooling, the powder was ground and sieved to obtain high-entropy catalyst powder.
[0073] Step 2, catalyst particles: Mix the powder obtained in Step 1 with 9 wt% PVA solution, add 5 wt% corn starch, and pass the mixture through a 60-mesh sieve; press the powder at 10 MPa for 1 min to form a sheet-like preform, crush it, and then pass it through 16, 18, 24, 30, and 45 mesh sieves for grading, and take 1.25-0.40 mm particle preforms.
[0074] Step 3: The billet is heated to 500℃ in a high-temperature electric furnace at a heating rate of 5℃ / min and held for 120 min. Then, it is heated to 900℃ at a heating rate of 5℃ / min and held for 1 h. Finally, it is cooled to 500℃ and allowed to cool naturally to obtain high-entropy catalyst particles.
[0075] The diameter range of catalyst particles in experiments 9-12 is shown in Table 5.
[0076]
[0077] (2) Test indicators and result analysis Specific surface area and pore size analysis: As shown in Table 6, with the decrease in the size of the high-entropy catalytic particles, the specific surface area of the sample decreased from 9.687 m². 2 / g gradually increased to 11.952 m 2 / g, while the pore size and pore volume remained basically stable. This indicates that adjusting the particle size mainly changed the macroscopic particle scale of the material, but did not significantly alter its intrinsic microscopic porosity characteristics.
[0078] Table 6. Pore structure parameters of experiments 9-12
[0079] Catalytic performance and stability analysis: From Figure 8 The data shows that the catalytic degradation efficiency of ciprofloxacin gradually increases with decreasing catalyst particle size. Experiment 12 exhibits the highest degradation rate constant, significantly better than Experiment 9. This is because the smaller particle size effectively shortens the diffusion path of reactant molecules, reduces mass transfer resistance, and promotes the reaction to extend from the particle surface to deeper internal structures, thereby significantly improving the utilization rate of active sites. Figure 8 The data shows that the cyclic stability of the catalyst significantly increases with the increase of particle size. Among them, Experiment 9 showed the lowest mass loss rate and the most intact morphology after multiple cycles, while Experiment 12 showed a more obvious mass loss. This is because the increase in particle size enhances the overall structural continuity and mechanical strength of the material, effectively resisting shear and collision effects during the reaction process, making it less prone to breakage, thereby improving the cyclic stability of the material in practical engineering applications.
[0080] Experiments 13-17: Effects of different pore-forming agent dosages on catalytic performance (1) Test methods A high-entropy catalyst particle, the preparation method of which includes the following steps: Step 1: Preparation of high-entropy catalyst powder: 5.04 g of MgO, 10.03 g of Co2O3, 9.34 g of NiO, 10.17 g of ZnO, and 9.98 g of Fe2O3 were weighed and mixed, and then mixed with anhydrous ethanol and zirconium oxide balls at a mass ratio of 1:3:5. The mixture was ball-milled in a planetary ball mill for 6 h. After drying, the powder was ground and sieved to obtain the raw material powder. The powder was placed in a corundum crucible and heated to 900℃ in a muffle furnace for 1 h. After natural cooling, the powder was ground and sieved to obtain the high-entropy catalyst powder. Step 2, Preparation of catalyst particles: The powder obtained in Step 1 is mixed with corn starch as a pore-forming agent and 9 wt% PVA solution, and then sieved. The powder is pressed into sheet-like blanks at 5 MPa for 1 min, crushed, and then graded through 24-mesh and 30-mesh sieves to obtain 0.80-0.60 mm particle blanks.
[0081] Step 3: The billet is heated to 500℃ in a high-temperature electric furnace at a heating rate of 5℃ / min and held for 30 min. Then, it is heated to 900℃ at a heating rate of 5℃ / min and held for 4 h. Finally, it is cooled to 500℃ and allowed to cool naturally to obtain high-entropy catalyst particles.
[0082] The content of pore-forming agent in experiments 13-17 is shown in Table 7.
[0083]
[0084] (2) Test indicators and result analysis Specific surface area (m²) of high-entropy catalyst particles prepared with different amounts of pore-forming agent 2 / g), pore size (nm) and pore volume (cm³) 3 The test results ( / g) are shown in Table 8.
[0085] Table 8. Pore structure parameters of experiments 13-17
[0086] Specific surface area and pore size analysis: Table 8 shows that with the increase of pore-forming agent content, the specific surface area, pore volume, and average pore size of the high-entropy catalytic particles first increase and then decrease. In experiment 15, the specific surface area increased to 11.167 m². 2 / g, and formed a uniformly distributed mesoporous network. This is because: within a medium content range, the gas release generated by the pore-forming agent matches the framework rearrangement process, which is conducive to the formation of a pore structure with good connectivity; while when the content of the pore-forming agent is too high, the violent gas release will cause the pore walls to thin or even collapse, causing the pore structure to coarsen, thereby leading to a decrease in specific surface area.
[0087] Catalytic performance and stability analysis: From Figure 9The data shows that the catalytic activity of the samples with added pore-forming agents was generally better than that of the samples without pore-forming agents. Among them, shiy 15 exhibited the fastest degradation rate in the early stage of the reaction, demonstrating the best reaction kinetics. This is because an appropriate amount of pore-forming agent significantly increases the porosity of the particles, optimizes the mass transfer efficiency of reactants within the particles, and increases the exposure of effective active sites. Figure 9 The data shows that the cycle stability of the catalytic material decreases with increasing pore-forming agent content. Experiment 13 showed the lowest mass loss, while Experiment 17 showed a significant increase in mass loss. This is because the high-porosity framework is more prone to breakage under stirring and impact. In summary, Experiment 15 improved catalytic activity while maintaining good reaction stability, achieving the optimal balance between porosity optimization and structural strength.
[0088] Experiment 18: Verification of the number of times high-entropy catalyst particles can be recycled (1) Test methods A high-entropy catalyst particle, the preparation method of which includes the following steps: Step 1: Preparation of high-entropy catalyst powder: 5.04 g of MgO, 10.03 g of Co2O3, 9.34 g of NiO, 10.17 g of ZnO, and 9.98 g of Fe2O3 were weighed and mixed, and then mixed with anhydrous ethanol and zirconium oxide balls at a mass ratio of 1:3:5. The mixture was heated to 1000℃ in a muffle furnace and held for 1 h. After drying, the mixture was ground and sieved to obtain raw material powder. The powder was placed in a corundum crucible and heated to 900℃ in a muffle furnace and held for 1 h. After natural cooling, the mixture was ground and sieved through a 60-mesh sieve to obtain high-entropy catalyst powder.
[0089] Step 2, Preparation of catalyst particles: The powder obtained in Step 1 is mixed with corn starch and 6 wt% PVA solution, and then passed through a 60-mesh sieve. The powder is pressed into sheet-like blanks at 10 MPa for 1 min, crushed, and then graded through 24-mesh and 30-mesh sieves to obtain 0.80-0.60 mm particle blanks.
[0090] Step 3: The billet is heated to 500℃ in a high-temperature electric furnace at a heating rate of 5℃ / min and held for 120 min. Then, it is heated to 900℃ at a heating rate of 5℃ / min and held for 12 h. Finally, it is cooled to 500℃ and allowed to cool naturally to obtain high-entropy catalyst particles.
[0091] (2) Effect of the number of recycling cycles on high-entropy catalyst particles The high-entropy catalyst particles prepared in Experiment 15 were used in a simulated wastewater degradation experiment of ciprofloxacin solution. After one experiment, the catalyst particles were recovered, and then another ciprofloxacin solution simulated wastewater degradation experiment was conducted. The high-entropy catalyst particles were reused 5 times. The results are shown in […]. Figure 10The data shows that Experiment 15 has an extremely high reusability rate, with an initial degradation rate of 97.0% and a remaining rate of 94.1% after five reuses. Combined with the metal ion dissolution data in Table 9, it can be seen that the dissolution concentration of each metal element is extremely low during the cycling process and gradually decreases with increasing cycle number; for example, Co decreases from 0.851 mg / L to 0.494 mg / L. This indicates that only a small amount of surface-unstable components migrate in the initial stage of the reaction. As the active surface tends to reach equilibrium, the system enters a highly stable state, confirming that the catalytic material is dominated by solid-phase catalysis, effectively reducing the risk of secondary pollution.
[0092] Table 9. Metal ion leaching concentrations in five cycles of Experiment 15
[0093] XRD characterization of Experiment 15 before and after cycling showed that the diffraction peak positions were basically consistent, with no new phase or significant peak shift. This indicates that after granulation and multiple catalytic reactions, the main crystal structure of the material remained stable, without significant phase reconstruction. The experiment demonstrates that the biphase structure formed through temperature control in the early stage possesses excellent chemical stability and can provide a solid framework for the catalytic reaction.
[0094] SEM observation of the particle morphology before and after cycling revealed that after multiple cycles, the overall morphology of the experimental particles remained intact, with only slight surface roughening in localized areas. This indicates that the formed particles maintained their main shape under stirring and collision conditions without breaking or collapsing. The experiment demonstrates that the granulation process employed in this invention effectively enhances the mechanical strength of the material, confining structural evolution to the surface region and ensuring the macroscopic stability of the material.
[0095] In summary, Experiment 15 exhibited significant structural stability during cycling. This stability was achieved through two-phase frameworks formed by temperature control, ensuring crystalline phase integrity, and granulation, which effectively enhanced physical strength to resist mechanical wear. This synergistic effect of multi-scale structures enabled the particulate catalyst to effectively prevent structural collapse during long-term operation, thus achieving highly efficient and durable catalytic performance.
[0096] The above description, in conjunction with specific embodiments, provides a further detailed explanation of this application and should not be construed as limiting the specific implementation of this application to these descriptions. Those skilled in the art to which this application pertains can make several simple deductions or substitutions without departing from the concept of this application.
Claims
1. A high-entropy catalyst, characterized in that: It consists of a framework material and a surface electronic environment conditioning material; The framework material includes MgO, Co3O4, NiO and ZnO; The surface electronic environment conditioning material is at least one of CuO, MnO2 and Fe2O3.
2. The high-entropy catalyst according to claim 1, characterized in that: The amount of the surface electronic environment conditioning material is 15-35 wt% of the weight of the frame material.
3. The high-entropy catalyst according to claim 1, characterized in that: The framework material is composed of MgO, Co3O4, NiO and ZnO; Optionally, the weight ratio of MgO, Co3O4, NiO and ZnO is 1:(1.6~2.6):(1.4~2.4):(1.6~2.6).
4. The high-entropy catalyst according to any one of claims 1-3, characterized in that: The high-entropy catalyst has a particulate structure; Optionally, the high-entropy catalyst is a porous particle; Optionally, the pore size of the high-entropy catalyst particles with porous structure is 12-55 nm; Optionally, the pore volume of the high-entropy catalyst particles with porous structures is 0.01-0.09 cm³. 3 / g; Optionally, the particle size of the high-entropy catalyst particles is 0.4-1.25 mm.
5. The method for preparing the high-entropy catalyst according to any one of claims 1-4, characterized in that: Includes the following steps, (1) Obtain the oxide powders of the framework material and the surface electronic environment conditioning material, mix them, and obtain the high-entropy catalyst powder; (2) Mix the high-entropy catalyst powder with the pore-forming agent to obtain a mixed powder. Press the mixed powder into tablets to obtain a sheet-like blank. Crush the sheet-like blank and classify and sieve it according to the required particle size of the high-entropy catalyst particles to obtain a particle blank. (3) Heat treatment is performed on the particle blank, that is, the temperature is raised to 500-550 ℃ at 2-20 ℃ / min and held for 20-120 min, then the temperature is raised to 700-1100 ℃ at 2-20 ℃ / min and held for 1-12 h, then the temperature is lowered to 500-550 ℃, and then the temperature is lowered to room temperature to obtain high entropy catalyst particles.
6. The preparation method according to claim 5, characterized in that: Step (1) also includes mixing the various oxide powders, dispersion media and grinding balls at a mass ratio of 1: (2~4): (4~6) and ball milling at a speed of 200-600 r / min for 4-24 hours to achieve preliminary mixing and refining of the raw materials; After ball milling, the mixture is dried, ground, and passed through a 40-100 mesh sieve to obtain raw material powder; The raw material powder is heated to 700-1100 ℃ at a heating rate of 2-20 ℃ / min for 1-4 hours for heat treatment. After natural cooling, the sintered product is thoroughly ground and passed through a 40-100 mesh sieve to finally obtain high-entropy catalyst powder.
7. The preparation method according to claim 5, characterized in that: In step (2), the pore-forming agent is corn starch; Optionally, the amount of the pore-forming agent is 3-9 wt% of the total weight.
8. The preparation method according to claim 5, characterized in that: In step (2), the tableting process is performed under pressure of 1-20 MPa for 1-5 min.
9. The application of the high-entropy catalyst according to any one of claims 1-4 in the activation of persulfate degradation of ciprofloxacin.
10. A reagent for activating persulfate, characterized in that: Contains the high-entropy catalyst according to any one of claims 1-4.
